2020
DOI: 10.36560/13820201046
|View full text |Cite
|
Sign up to set email alerts
|

Different types of herbicides in inducing the hormetic effect on soybean culture

Abstract: The objective of this study was to evaluate the effect of 2,4-D and chlorimuron-ethylunderdosage on the soybean hormesis effect. The study was conducted in the facilities of the University Center of Vale do Araguaia (UNIVAR), in Barra do Garças, MatoGrosso. Was used or the randomized block design (DBC) with five replications for each treatment, where an experiment was performed for 2,4-D and another forchlorimuron ethyl. The treatments used were: 2,4-D (0, 5, 10, 15 and 20g ea ha-1) and Ethyl Chlorimuron (0.4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The use of this substance proved to be promising, as it resulted in an increase in plant height and soybean yield compared to the control, without application, being the only herbicide to cause such an effect. Silva et al (2020) observed similar results, with an increase in dry mass and height of soybean plants after chlorimuron application of 0.4 g ai ha -1 . However, studies that report an increase in yield through the use of subdoses of chlorimuron are scarce, which reinforces the relevance of the results of the present study.…”
Section: /6supporting
confidence: 73%
“…The use of this substance proved to be promising, as it resulted in an increase in plant height and soybean yield compared to the control, without application, being the only herbicide to cause such an effect. Silva et al (2020) observed similar results, with an increase in dry mass and height of soybean plants after chlorimuron application of 0.4 g ai ha -1 . However, studies that report an increase in yield through the use of subdoses of chlorimuron are scarce, which reinforces the relevance of the results of the present study.…”
Section: /6supporting
confidence: 73%